Konstruksi Sosial Healthy Lifestyle dalam Budaya Fitness Gen Z di Lingkungan Perguruan Tinggi - Calvin Adiputra Djaja; Diah Ayu Candraningrum (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The growing awareness of healthy lifestyles among Generation Z has increased alongside concerns for physical health, mental well-being, and self-identity, particularly within urban and university environments. Fitness communities have emerged not only as spaces for physical exercise but also as social arenas where values, norms, and identities are collectively shaped. This study aims to understand how Generation Z students at Universitas Tarumanagara (UNTAR), Jakarta, construct the meaning of a healthy lifestyle through their involvement in fitness communities. Using a qualitative approach with a case study method, this research explores participants’ lived experiences in engaging in fitness activities, developing healthy routines, and interpreting a healthy lifestyle as part of their self-identity. Data were collected through in-depth interviews, non-participant observation, and social media documentation. The analysis was guided by Berger and Luckmann’s Social Construction of Reality theory, focusing on the processes of externalization, objectivation, and internalization. The findings reveal that a healthy lifestyle is not merely understood as maintaining physical health but also as a symbol of discipline, mental balance, and social existence. Fitness communities function as social spaces that strengthen motivation, emotional support, and the internalization of healthy living values. This study highlights that healthy lifestyles among Generation Z are socially constructed through personal experiences and community dynamics. Perkembangan gaya hidup sehat di kalangan Generasi Z semakin menguat seiring meningkatnya kesadaran terhadap kesehatan fisik, mental, dan citra diri, khususnya di lingkungan perkotaan dan kampus. Komunitas fitness menjadi salah satu ruang sosial yang tidak hanya memfasilitasi aktivitas kebugaran, tetapi juga membentuk nilai, norma, dan identitas generasi muda. Dalam konteks tersebut, penelitian ini bertujuan memahami bagaimana mahasiswa Generasi Z Universitas Tarumanagara (UNTAR) Jakarta mengonstruksi makna healthy lifestyle melalui keterlibatan mereka dalam komunitas fitness. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus untuk menggali pengalaman langsung anggota komunitas dalam menjalankan aktivitas kebugaran, membentuk rutinitas sehat, serta memaknai gaya hidup sehat sebagai bagian dari identitas diri. Data dikumpulkan melalui wawancara mendalam, observasi non-partisipan, dan dokumentasi media sosial. Analisis data dilakukan dengan mengacu pada Teori Konstruksi Realitas Sosial Berger dan Luckmann yang menekankan proses eksternalisasi, objektivasi, dan internalisasi. Hasil penelitian menunjukkan bahwa healthy lifestyle tidak hanya dimaknai sebagai upaya menjaga kesehatan fisik, tetapi juga sebagai simbol kedisiplinan, keseimbangan mental, serta eksistensi sosial. Komunitas fitness berperan sebagai ruang interaksi yang memperkuat motivasi, dukungan emosional, dan internalisasi nilai-nilai hidup sehat. Temuan ini menegaskan bahwa gaya hidup sehat bagi Generasi Z merupakan konstruksi sosial yang terbentuk melalui pengalaman personal dan dinamika komunitas.